Introduction to the design and behavior of bolted joints - Bickford, John H. (Mechanical engineering, 2008)
Offers comprehensive information on the design and behavior of non-gasketed bolted joints. This book features a chapter on ways to control preload including the developments in ultrasonic and stretch control. It also features a materials chapter as well as sections on structural steel joins, airframe joints, and vibration resistance fasteners.